Creating the Conditions for Climate Resilience: A Community-Based Approach in Canumay East, Philippines - Cash, Corrine (2021)
People who reside in informal settlements in the Global South are most vulnerable to extreme weather events and their consequences, such as flooding, landslides, and fires. Those located in coastal areas face severe challenges from seasonal and typhoon-induced flooding. Research shows that uncertain land rights exacerbate community vulnerability because residents are under constant threat of eviction by private sector actors or the state. Individual and community upgrading is rarely possible in such a situation. This article focuses on the efforts to secure tenure and upgrade their community by the residents of Sitio Libis, located in Canumay East, City of Valenzuela, Philippines. The study demonstrates that while community-based approaches require skills and capacities of community members, enabling conditions created by government and/or NGOs are required for transformational outcomes. While the people of Sitio Libis did not conceptualize their efforts in terms of climate change adaptation, their success suggests the possibility for smart partnerships among state-civil society/private sector actors to emerge in support of small-scale climate action.